Kembalinya Konservatisme Islam Indonesia - Wahid, Din (Studia Islamika, 2014)
Martin van Bruinessen, ed, Contemporary Development in Indonesian Islam, Explaining the “Conservative Turn”, Singapore: Institute of Southeast Asian Studies, 2013, pp. 240 + xxxiv.Contemporary Developments in Indonesian Islam: Explaining the ‘Conservative Turn’ consists of four articles analyzing conservative currents among Muslims in Indonesia. The  book’s first two articles deal with established Muslim organizations, namely the Council of Indonesian ‘Ulama (MUI) and Muhammadiyah, while the other two discuss radical Islamic movements in the regions of South Celebes and Solo, Central Java. Written by van Bruinessen, the book examines why the conservative trend has reemerged in Indonesian Islam. The author provides readers with two theories. Firstly, he argues that a decline in the influence of liberal thought has accompanied the democratization process. Secondly, he identifies an increase of Middle Eastern influence to Indonesia through alumni. This work shows that conservatism is not only apparent in radical Islamic movements that have emerged during the Reformation era but also present in well-established organizations such as MUI and Muhammadiyah. The significance of this work to the study of Indonesian Islam lies in its explanation of how conservatism enters those organizations.DOI: 10.15408/sdi.v21i2.1043